Creation of a refractive lens within an existing intraocular lens using a femtosecond laser. Issue 8 (August 2016) - Sahler, Ruth; Bille, Josef F.; Enright, Sean; Chhoeung, Somaly; Chan, Kevin
Abstract : Purpose : To assess the efficiency and effectiveness of the technology that creates a hydrophilicity‐based refractive index change within a standard intraocular lens (IOL) to alter the refractive characteristics of the IOL. Setting : Perfect Lens LLC, Irvine, California, USA. Design : Experimental study. Methods : The IOL used in this experiment was a standard hydrophobic model (EC‐1Y). The refractive index of the material was changed by exposure of the material to a femtosecond laser and the subsequent absorption of water by the material. An experimental system using a femtosecond laser, an acoustic‐optic modulator, beam‐shaping optics, a scan system, and an objective lens was used to create the refractive index change within the IOL. Experiments were performed to determine the optimum wavelength, energy per pulse, and line spacing to produce the refractive index shaping lens. A power and modulation transfer function (MTF) measurement device for refractive and diffractive IOLs was used to measure the diopter and MTF before and after the creation of the refractive index shaping lens. Results : The technology successfully altered the refractive characteristics of the IOL. The refractive index change altered the diopter (D) of the IOL (to within ±0.1 D of the targeted change) without significant diminution in the MTF (<0.1 or MTF ≥0.51 for the 100 lp/mm measurement). Conclusion : The refractive properties of an IOL can be altered by building a refractive index shaping lens within an IOL using a femtosecond laser with minimal diminution in MTF. Financial Disclosure : All authors are employed by Perfect Lens, LLC and have a financial interest in the products of Perfect Lens, LLC.